2012
DOI: 10.1186/1471-2407-12-269
|View full text |Cite
|
Sign up to set email alerts
|

Expanded clinical and experimental use of SOX11 - using a monoclonal antibody

Abstract: BackgroundThe transcription factor SOX11 is of diagnostic and prognostic importance in mantle cell lymphoma (MCL) and epithelial ovarian cancer (EOC), respectively. Thus, there is an unmet clinical and experimental need for SOX11-targeting assays with low background, high specificity and robust performance in multiple applications, including immunohistochemistry (IHC-P) and flow cytometry, which until now has been lacking.MethodsWe have developed SOX11-C1, a monoclonal mouse antibody targeting SOX11, and succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…The pattern of staining was nuclear, as reported by other investigators in foetal brain tissue (Haslinger et al , 2009), mantle cell lymphoma (Nordström et al , 2012), ovarian carcinoma (Brennan et al , 2009) and medulloblastoma (de Bont et al , 2008), conforming to the nuclear localisation signals conserved among all Sox proteins. Indeed, the lack of nuclear staining reportedly correlates with the absence of Sox11 mRNA in normal and neoplastic tissues (Ek et al , 2008).…”
Section: Discussionsupporting
confidence: 83%
“…The pattern of staining was nuclear, as reported by other investigators in foetal brain tissue (Haslinger et al , 2009), mantle cell lymphoma (Nordström et al , 2012), ovarian carcinoma (Brennan et al , 2009) and medulloblastoma (de Bont et al , 2008), conforming to the nuclear localisation signals conserved among all Sox proteins. Indeed, the lack of nuclear staining reportedly correlates with the absence of Sox11 mRNA in normal and neoplastic tissues (Ek et al , 2008).…”
Section: Discussionsupporting
confidence: 83%
“…Proteins were blotted onto a PVDF membrane with the iBlot W Dry Blotting System (Invitrogen) and the membrane was blocked in 5% milk/PBS. SOX11 expression Sequence was originally derived from the HPR project as previously described [35]. was assessed using SOX11-C1 at a final concentration of 1 μg/ml in 5% milk/PBS.…”
Section: Evaluation Of the Sox11-c1 Antibody In Western Blot Using B mentioning
confidence: 99%
“…Furthermore, as most studies use IHC to assess SOX11 expression, it is worth mentioning that tissue fixation time could have a large impact on the staining intensity. Also, most studies have assessed SOX11 expression using polyclonal reagents, which display a potential cross-reactivity to SOX4 50 and/or suffer from batch variations. Thus, current literature supports the use of specific monoclonal SOX11 antibodies that today are present on the market.…”
Section: Sox11 As a Prognostic Toolmentioning
confidence: 99%
“…It has further been suggested that SOX11 may be used as a marker for minimal residual disease. 50 Analysis of SOX11 protein, being highly homologous to other SOX4 and SOX12, has been hampered by unspecific tools and only recently a specific monoclonal antibody was developed. 50 The superiority of this antibody has also been confirmed by independent users.…”
Section: Sox11 and Its Role As A Routine Diagnostic Tool In MCLmentioning
confidence: 99%
See 1 more Smart Citation